Study of in vitro bioactivity and mechanical properties of diopside nano-bioceramic synthesized by a facile method using eggshell as raw material - Kazemi, Amirhossein; Abdellahi, Majid; Khajeh-Sharafabadi, Armina; Khandan, Amirsalar; Ozada, Neriman (Elsevier Science Bv, 2017)
In this study, diopside bioceramic was synthesized using a mechanical milling process and subsequent heat treatment. The simplicity of experiments and also the high energy available in ball milling lead to rapid synthesis of the products in comparison with other synthesis methods. Magnesium oxide (MgO), silicon dioxide (SiO2) and eggshell (as the calcium source) powders were weighted in stoichiometric conditions and milled to initial activation of the surface of the powder's mixture. Then a sintering process was conducted to complete formation of diopside nanopowder and also evaluates its thermal stability. The mechanisms occurred during the synthesis of this bioceramic were carefully investigated. X-Ray diffraction analysis (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), thermogravimetry (TG), differential thermal analysis (DTA), and inductive coupled plasma atomic emission spectroscopy (ICP-AES) were used for gathering and analyzing data. The ability and rate of apatite formation on the sample surface were evaluated by Simulated Body Fluid (SBF) test, a method that is well recognized to characterize the in vitro bioactivity of ceramic materials. According to the results obtained, the diopside samples had a significant potential to form apatite layer on their surface during soaking in the SBF solution. Besides, the bonding strength of this bioceramic was about 350 +/- 7 MPa which was almost more than three times of that reported for hydroxyapatite. An excellent fracture toughness of 4 +/- 0.3 MPa m(0.5) was also obtained for this ceramic which was higher than that of previously reported works. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Diopside; Nanopowder; Mechanical properties; Milling